Ethno-nationalist at last? Scholarly views on the essence of Russian nationalism today (KULT_online, 2016)
The book The New Russian Nationalism: Imperialism, Ethnicity and Authoritarianism 2000-15 by Pål Kolstø and Helge Blakkisrud sets out to investigate a complex issue pertaining to the essence of Russian nationalism. It brings together twelve scholars from different countries to trace the vicissitudes of Russian nationalism over the last decade and a half from various angles – economic, political, religious, and societal. By consulting self-conducted public opinion polls, the book seeks to demonstrate a recent turn in Russian nationalism, which became more pronounced in light of the dramatic events in the Ukraine. The edited volume provides valuable, well-researched perspectives and could serve as a good introduction for those less familiar with the subject of Russian nationalism.